Morphological characterization and thermal properties of compatibilized poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV)/poly(butylene succinate) (PBS)/halloysite ternary nanocomposites - Kennouche, Salim; Le Moigne, Nicolas (My University, 2015)
Blends of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) and poly(butylene succinate) (PBS) at different weight ratios (80/20, 50/50 and 20/80 w/w) and ternary PHBV/PBS/halloysite nanotubes (HNT) nanocomposites were prepared by melt compounding. Typical co-continuous and nodular morphologies were obtained with the neat blends. The effect of maleic anhydride-grafted PHBV (PHBV-g-MA) compatibilizer and HNT on the nodular microstructure and thermal properties of PHBV/PBS/HNT nanocomposites was investigated. Morphological observations using scanning electron microscopy (SEM) showed an improved dispersion of PBS nodules in the immiscible PHBV/PBS 80/20 blends, owing to the diffusion and emulsifying effect of PHBV-g-MA chains at the PHBV/PBS interface. A preferential location of HNTs in the PBS nodules was observed, due to their better wettability with PBS phase. Image analysis showed that combining HNT and compatibilizer led to a reduced emulsifying effect, attributed to the formation of PHBV-g-MA/HNT aggregates that limit the diffusion of PHBV-g-MA chains at the interface. Thermogravimetric analysis (TGA) and Pyrolysis Combustion Flow Calorimetry (PCFC) showed a better thermal stability and fire reaction of PHBV in the PHBV/PBS blends as compared to neat PHBV. Incorporation of HNT in the blends decreased their thermal stability but improved significantly their fire reaction, whereas combining PHBV-g-MA and HNT seems to level the influence of each component.
Keywords: Nanocomposite Halloysite Polymer blend Poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) Poly(butylene succinate) (PBS)